1970
DOI: 10.3329/ujzru.v27i0.1965
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of fishes and non-fin fishes of the river Padma near Rajshahi, Bangladesh

Abstract: No Abstract doi:10.3329/ujzru.v27i0.1965 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 99-100

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 1 publication
0
10
1
Order By: Relevance
“…Hussain and Manohar, 2016 , Hussain and Manohar, 2017 and Sarkar et al (2012b) reported that M. lamarrei was a continuous breeder from Bhopal and West Bengal in India respectively, which is also almost similar to our findings. Whereas, Bhuiyan et al (2008) recorded spawning season was April-June from Rajshahi, Bangladesh and Paul (2001) reported May-August from Natore, Bangladesh which is dissimilar to our present study. Hussain and Manohar, 2016 , Hussain and Manohar, 2017 reported two peak seasons (May–June and November–December) in a year for M. lamarrei from Bhopal, India.…”
Section: Discussioncontrasting
confidence: 99%
“…Hussain and Manohar, 2016 , Hussain and Manohar, 2017 and Sarkar et al (2012b) reported that M. lamarrei was a continuous breeder from Bhopal and West Bengal in India respectively, which is also almost similar to our findings. Whereas, Bhuiyan et al (2008) recorded spawning season was April-June from Rajshahi, Bangladesh and Paul (2001) reported May-August from Natore, Bangladesh which is dissimilar to our present study. Hussain and Manohar, 2016 , Hussain and Manohar, 2017 reported two peak seasons (May–June and November–December) in a year for M. lamarrei from Bhopal, India.…”
Section: Discussioncontrasting
confidence: 99%
“…In fact, due to some recent incentive-based management measures, the abundance of fish species has remarkably increased and fishers get more species in their catches (Islam et al, 2016;Islam et al, 2017). However, the recorded fish species was much lower than some other rivers of Bangladesh (Bhuiyan et al, 2008;Rahman et al, 2012;Hossian et al, 2014). Hossian et al, 2014 found 128 species belonging to 12 orders and 35 families from the flood plain area of greater Noakhali areas, so the species richness was much higher than that of the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…Two villages-Andharmanik and Dhulsura under Harirampur upazila (sub-district) of this district were selected as the study sites. These villages are located on the Padma riverbank ( Figure 2) which is already affected by climate variability and changes (Islam 2004;Bhuiyan et al 2008;Vineis et al 2011). Therefore, the impacts of climate variability and changes on the Padma River consequently affected…”
Section: Study Sitesmentioning
confidence: 99%